Targeted therapy combined with immunotherapy in patients with breast infiltrating ductal carcinoma with axillary lymph node metastasis of metaplastic SCC - Rilan Bai; Lin Jia; Yangyang Gao; Xu Sun; Naifei Chen; Zheng Lv; Jiuwei Cui (Thoracic Cancer, 2022)
Abstract At present, the clinicopathological features, optimal treatment patterns, and prognosis of breast metaplastic squamous cell carcinoma (SCC) are not fully understood and are still controversial. Here, we report a 56‐year‐old female patient with breast infiltrating ductal carcinoma with axillary lymph node metastasis of metaplastic SCC admitted to our hospital. Their homology was clarified by comparing the gene mutation results of the two lesions, that is, the axillary lymph node lesion was a metastasis of breast metaplastic SCC. We treated the patient with Poly ADP‐ribose Polymerase (PARP) inhibitors in combination with immune checkpoint inhibitors (ICIs) and found that she could achieve clinical benefit from the combination regimen. We reported a successful diagnosis and treatment of this rare refractory disease and reviewed the literature on the characteristics, pathogenesis, and advances in the diagnosis and treatment of breast metaplastic SCC.